2013
DOI: 10.5858/arpa.2013-0012-oa
|View full text |Cite
|
Sign up to set email alerts
|

Reducing False-Negative and False-Positive Diagnoses in Anatomic Pathology Consultation Material

Abstract: Context.-Previous studies have shown that there are disagreements in interlaboratory consultation, including false-negative and false-positive diagnoses. To date, methods to reduce false-negative and false-positive diagnoses have been poorly documented.Objective.-To identify features associated with falsenegative and false-positive diagnoses in anatomic pathology.Design.-We reviewed the results of interlaboratory consultation in our institution during a 9-year period. For false-negative and false-positive diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…Several studies addressed the role of a second opinion in surgical pathology material and analyzed the discordances between the initial (outside) and reviewed (in‐house) diagnoses. According to these studies, diagnostic discrepancies that resulted in change of clinical management and/or therapy for the referred patient ranged from 1.2% to 5.8% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies addressed the role of a second opinion in surgical pathology material and analyzed the discordances between the initial (outside) and reviewed (in‐house) diagnoses. According to these studies, diagnostic discrepancies that resulted in change of clinical management and/or therapy for the referred patient ranged from 1.2% to 5.8% …”
Section: Introductionmentioning
confidence: 99%
“…There are some anatomical sites that are more prone to diagnostic disagreements, including the gastrointestinal, genitourinary, female genital tract, hematolymphoid system, serosal surface, skin, and breast sites. The thyroid gland is the anatomic site that showed the highest rate of disagreement in a study that analyzed the second‐opinion diagnosis of head and neck lesions .…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies included consecutively recruited or randomly selected or stratified samples;9 13 19 23 25 32 33 43 51 53 55 60 six studies included enriched samples;20 21 27 42 45 56 nine studies included only cases selected for a second opinion 30 31 34 37 40 44 57–59…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed the agreement between two readers;33 43 in 1 study19 three readers reviewed slides; in 15 studies this information was not reported;9 23 30 31 34 37 40 44 45 53 55 57–60 in 9 studies, the same set of slides were reviewed by 10,32 12,20 27 31,21 47,13 26,51 220–46625 and 186–251 pathologists 42. Elmore et al reported agreement among the initial independent diagnoses of three expert consensus panel members (CPM), and the concordance between 115 pathologists and the consensus-derived reference diagnosis 56.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation